PENGARUH KEPEMILIKAN ASINGDAN KOMITE AUDIT INDEPENDEN TERHADAP TRANSPARANSI INFORMASI - Nopiyanti, Anita (Universitas 17 Agustus 1945 Jakarta, 2019)
This study aims to see whether there are influence of Foreign Ownership, Profitability, and Independent Audit Committee On Information of Transparency. This Study uses the companies listed on Indonesian Stock Exchange (BEI) in 2013, 2014, and 2015. Sampling technique using purposive sampling (purposive sampling method). Selection of a sample of 151 manufacturing companies listed in Indonesia Stock Exchange resulted in 42 companies that are acceptable. and testing the hypothesis is used multiple linear regression analysis with SPSS 21 and a significance level of 5% (0,05). The results of the testing showed that: (1) there is no significant influence of foreign ownership as measured by proportion preferred stock had foreign institution on information of transparency with a significance level of 0.153 is greater than the specified level α = 0.05, (2) there is no significant influence of independent audit committe as measured by proportion membership of independence on information of transparency with a significance level of 0.516 is greater than the specified level α = 0.05.